Classic African American women's narratives - Andrews, William L., 1946- (Oxford University Press, 2003)
This book offers teachers, students, and general readers a one-volume collection of the most memorable and important writing in prose by African American women before 1865. The book reproduces in one volume the canon of African American women's fiction and autobiography during the slavery era in U.S. history. Each text in the volume represents a "first." Maria Stewart's Religion and the Pure Principles of Morality (1831) was the first political tract authored by an African American woman. Jarena Lee's Life and Religious Experience (1836) was the first African American woman's spiritual autobiography. The Narrative of Sojourner Truth (1850) was the first slave narrative to focus on the experience of a female slave in the United States. Frances E.W. Harper's "The Two Offers" (1859) was the first short story published by an African American woman. Harriet E. Wilson's Our Nig (1859) was the first novel written by an African American woman. Harriet Jacob's Incidents in the Life of a Slave Girl (1861) was the first autobiography authored by an African American woman. Charlotte Forten's "Life on the Sea Islands" (1864) was the first contribution by an African American woman to a major American literary magazine (the Atlantic Monthly). Complemented with an introduction by William L. Andrews, this is the only one-volume collection to gather the most important works of the first great era of African American women's writing